Anticipating the Threat of Democratic Majoritarianism: Ambedkar on Constitutional Design and Ideology Critique, 1941–1948. (June 2023) - Govind, Rahul
This article analyses B. R. Ambedkar's works written between 1941 and 1948, and it discerns a central set of concerns and arguments in this otherwise diverse corpus. It argues that since universal franchise as a political principle is uncontroversial, Ambedkar's primary concern is geared towards the danger of democratic majoritarianism in a society riven by historically, legally and ideologically determined forms of inequality and their logic—a danger that can only be addressed at the dual levels of institutional design and ideological critique. Reading together Pakistan or the Partition of India and What Congress and Gandhi have done to the Untouchables, the initial sections argue that Ambedkar was critical of Congress and Muslim league politics because he saw in them both, albeit in distinct ways, the affirmation of religious identity as central to the formulation of political identity. Such an orientation, in the actual mechanics of mass politics and constitutional negotiation, is therefore read as inevitably leading to conflicts including demands for Partition, but at the same time such politics avoided fundamental questions of internal critique and instituted forms of socialized inequality. It is in this context, and the imminence of Partition, that the article analyses Ambedkar's argument for the need of both a specific institutional design (constitutional provisions) and an ideology critique (his historical research including Who were the Sudras and The Untouchables ). The analysis of the demand for partition and the category of the minority can only be understood through Ambedkar's acute historical and theoretical understanding of the nation and its history, as well as the normative demands required for institutional justice, as will be shown through a reading of this corpus.